Influence of socioeconomic factors and distance to radiotherapy on breast‐conserving surgery rates for early breast cancer in regional Australia; implications of change. Issue 5 (21st November 2017) - Collins, Ian M.; Lum, Caroline; Versace, Vincent L.
Abstract: Aims: Breast conserving surgery rates are affected by many factors including distance to radiotherapy and tumor‐related features. Numerous studies have found women who must travel further for radiotherapy are more likely to choose mastectomy and avoid radiotherapy. We examined relationships between socioeconomic group, distance to radiotherapy services and mastectomy rates across a range of rural and metropolitan settings. Methods: We used a dataset extracted from the Evaluation of Cancer Outcomes Barwon South Western Registry, which captured data on new breast cancer diagnoses in the southwest region of Victoria, Australia. Using logistic regression, we modeled treatment choice of women with early breast cancer (mastectomy vs breast conserving surgery) using explanatory variables that included distance to radiotherapy, and area‐level socioeconomic data from the Australian Bureau of Statistics, while controlling for clinical factors. Results: Mastectomy was associated with tumor size, nodal burden and younger age at surgery. Distance to a radiotherapy center was also strongly associated with increased rates of mastectomy for women who traveled 100–200 km for radiotherapy (odds ratio = 1.663; P  = 0.03) compared to the reference group who were within 100 km of radiotherapy. No socioeconomic differences were seen between the two groups. Conclusion: A strong association between distance to radiotherapy and the type of surgery for early breast cancer was found. Improving access to radiotherapy therefore has the potential to improve breast cancer outcomes for women in regional Australia.